Improving Basic Services for the Bottom Forty Percent : Lessons from Ethiopia - Khan, Qaiser M.; Faguet, Jean-Paul; Gaukler, Christopher; Mekasha, Wendmsyamregne (Washington, DC: World Bank, 2014)
Ethiopia, like most developing countries, has opted to deliver services such as basic education, primary health care, agricultural extension advice, water, and rural roads through a highly decentralized system (Manor 1999; Treisman 2007). That choice is based on several decades of theoretical analysis examining how a decentralized government might respond better to diverse local needs and provide public goods more efficiently than a highly centralized government. Ethiopia primarily manages the delivery of basic services at the woreda (district) level. Those services are financed predominantly through intergovernmental fiscal transfers (IGFTs) from the federal to the regional and then the woreda administrations, although some woredas raise a small amount of revenue to support local services. Since 2006, development partners and the government have cofinanced block grants for decentralized services through the Promoting Basic Services (PBS) Program. Aside from funding the delivery of services, the program supports measures to improve the quality of services and local governments capacity to deliver them by strengthening accountability and citizen voice.